2022
DOI: 10.3389/fcvm.2021.809885
|View full text |Cite
|
Sign up to set email alerts
|

A Preclinical Rat Model of Heart Failure With Preserved Ejection Fraction With Multiple Comorbidities

Abstract: Heart failure with preserved ejection fraction (HFpEF) is a common complex clinical syndrome for which there are currently few evidence-based therapies. As patients with HFpEF very often present with comorbidities comprising the metabolic syndrome, we hypothesized, that metabolic syndrome could lead over time to the development of diastolic dysfunction and HFpEF. Obesity-prone rats were exposed to high-fat diet and compared to obesity-resistant rats fed with standard chow. Phenotyping of metabolic syndrome, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 63 publications
1
7
0
1
Order By: Relevance
“…Several limitations of our study need to be considered. As mentioned before, the rat model of D-GAL-induced premature ageing we used in the study did not recapitulate all the cardiac changes, especially those related with diastolic dysfunction, described previously (Chang et al, 2016; Hubesch et al, 2022; Kim et al, 2023; Werner et al, 2018). This might have affected mostly the potentially beneficial effects of the P-EVs.…”
Section: Discussionmentioning
confidence: 99%
“…Several limitations of our study need to be considered. As mentioned before, the rat model of D-GAL-induced premature ageing we used in the study did not recapitulate all the cardiac changes, especially those related with diastolic dysfunction, described previously (Chang et al, 2016; Hubesch et al, 2022; Kim et al, 2023; Werner et al, 2018). This might have affected mostly the potentially beneficial effects of the P-EVs.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, some of the most compelling data indicated unchanged inflammatory cells infiltration in myocardium whereas the circulating inflammatory biomarker sST2 was largely increased in a metabolic syndrome associated HFpEF rat model. Therefore, it cannot be excluded that other circulating inflammatory markers, which were not tested here, could be strongly activated ( Hubesch et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Animals used in the present study were diet‐induced obesity‐prone and obesity‐resistant Sprague Dawley rats raised using selected breeders obtained from Charles River Laboratories Inc. (Wilmington, MA). As previously reported, 13 experimental HFpEF associated with multiple comorbidities (ie, metabolic syndrome) was induced in 4‐week‐old obesity‐prone rats (n=13) fed with a high‐fat diet (473 kcal/100 g; 45% of energy from lipids and 17% from sucrose; D1245; Research Diets, New Brunswick, NJ) for 12 months. Nine 4‐week‐ old obesity‐resistant rats fed with a standard rat chow diet (339 kcal/100 g; 5% of energy from lipids and 2% from sucrose; A03 Safe Diets, Augy, France) for 12 months were used as controls.…”
Section: Methodsmentioning
confidence: 97%
“…In this context, we developed an experimental rat model of HFpEF associated with multiple comorbidities, as a robust preclinical model of HFpEF mimicking key features observed in patients including aging and comorbidities. 13 In the present study, we evaluated whether these rats developed PH and RV dysfunction as observed in patients with HFpEF and studied underlying pathophysiological mechanisms.…”
mentioning
confidence: 99%